Political Communication Strategy of the General Election Commission (KPU) of Kediri City for Increasing Public Political Participation in the 2024 Election - Siti Amanah; Nisa Fitriani (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This research aims to explain the political communication strategy of the KPU of Kediri City in increasing public political participation in the 2024 election and the supporting and inhibiting factors for the KPU and the people of Kediri City. This research uses a descriptive qualitative approach through observation, in-depth interviews, and documentation methods for collecting primary and secondary data in research. The subjects of this research are the team from the KPU of Kediri City (Its Secretary and Commissioner), an official institution responsible for organizing elections in Kediri City, and the people of Kediri City who are involved in the general election process in 2024. The results of this study indicate that the KPU's political communication strategy is through face-to-face socialization and online media, as well as the “goes to school” and “goes to campus” programs. The delivery of political messages has three stages: beginning, middle, and end. Increased public participation is seen in the percentage of community attendance at polling stations. Election indicators are seen after voting or election. In 2024, it reached 86.72 percent; from 2019 to 2024, the percentage of public participation increased by 0.53 percent. Supporting factors for the KPU are the voter pyramid and partnership with community organizations. In contrast, the inhibiting factors are the KPU's few internal human resources and schedules that conflict with other activities.